Video Wisata Virtual sebagai Media Promosi Desa Ekowisata Pancoh di Era Kenormalan Baru - Sushartami, Wiwik; Sari, Yulita Kusuma; Maizida , Karlina; Purwandani , Intan (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2021)
Following the announcement by the national government of the cases of the Covid-19 pandemic in March 2020, tourism activities in various destinations in Indonesia, including the Pancoh Ecotourism Village, as one of the partners of the UGM Tourism Studies Program, were immediately postponed. This condition impacted the local economic circulation as the income of the population decreased. In the background of this pandemic scenario, tourism operations will hopefully be resumed as soon as possible. The Community Service Program was therefore carried out in order to achieve the key objective; to create a promotional video for the Pancoh Ecotourism Village in preparation for re-operation under a new health protocol via collaborative work. The other goal of this Community Service Program is to fulfill the commitment to higher education through Tridarma. In addition, a Community Partnership was formed to assist the Pancoh Ecotourism Team in particular and the Village Community in general in the planning of post-pandemic tourism activities to encourage the sustainability of tourism in the village concerned. This program used Community-Based Participatory Action Research (CBPAR) which consists of five stages, from project design to reporting, as an approach. The results of the program include a video training program and a virtual video promotion of the Pancoh Ecotourism Village. Public engagement and institutional collaboration have been important and considered to be the key to success of this program. By the end of the program, video promotion will be released via the social media of Pancoh. ===== Menyusul pengumuman pemerintah pusat tentang kasus pandemi Covid-19 pada Maret 2020, kegiatan pariwisata di berbagai destinasi di Indonesia, termasuk Desa Ekowisata Pancoh, sebagai salah satu mitra Program Studi Pariwisata UGM, langsung ditunda. Kondisi ini berdampak pada peredaran ekonomi lokal seiring dengan penurunan pendapatan penduduk. Dengan latar belakang situasi pandemi ini, kegiatan pariwisata diharapkan dapat segera dilanjutkan. Oleh karena itu, Program Pengabdian kepada Masyarakat dilaksanakan untuk mencapai tujuan utama; membuat video promosi untuk Desa Ekowisata Pancoh dalam persiapan untuk beroperasi kembali di bawah protokol kesehatan baru melalui kerja kolaboratif. Tujuan lain dari Program Pengabdian kepada Masyarakat ini adalah untuk memenuhi komitmen pendidikan tinggi melalui Tridarma. Selain itu, kerjasama komunitas dibentuk untuk membantu Tim Ekowisata Pancoh pada khususnya dan Masyarakat Desa pada umumnya dalam perencanaan kegiatan wisata pasca pandemi untuk mendorong keberlanjutan pariwisata di desa yang bersangkutan. Program ini menggunakan Community-Based Participatory Action Research (CBPAR) yang terdiri dari lima tahap, mulai dari desain proyek hingga pelaporan, sebagai pendekatan. Hasil dari program ini antara lain program pelatihan video dan promosi video virtual Desa Ekowisata Pancoh. Keterlibatan publik dan kolaborasi kelembagaan menjadi penting dan dianggap sebagai kunci keberhasilan program ini. Di akhir program, video promosi akan dirilis melalui media sosial Pancoh.